Prediction of Compression Strength of Cold formed Steel Columns - Natashya, N.J.W. (ENCON 2008, 2008)
Abstract—Cold formed steel structures are fabricated from structural sections made by bending flat sheets at ambient temperatures into shapes which will support loads. They are currently designed based on “effective width” philosophy. The effective width philosophy is used in the British, European, American and Australian codes. The Direct Strength Method is a new design philosophy utilizing the buckling loads obtained from a buckling analysis. This method has been included in the American and Australian codes. The method has been calibrated using some standard sections. For other types of sections the design formula are applicable but with higher safety factors. The buckling analysis is carried out using finite strip method. A free software “CUFSM” is available for the buckling analysis. Only limited studies have been carried out in Malaysia on cold formed structures. Some limited compression tests on sections, of 500 mm and 1000 mm long lengths, available in Malaysia were carried out and the results analyzed. BS 5950 Part 5 is currently used in Malaysia for design of cold formed steel structures. This work examines the results of the experimental work reported in literature and compares it with the design load capacity obtained using provisions of BS code and the Direct strength method. Keywords: cold formed steel columns, Direct strength method, compression test, effective width method, buckling analysis